Dampak Program Peremajaan Kelapa Sawit Rakyat Terhadap Produktivitas dan Pendapatan Petani Kelapa Sawit di Kecamatan Gunung Megang Kabupaten Muara Enim - Tuteng Rohmansyah; Fifian Permata Sari; Enda Kartika Sari (LPPM Institut Pendidikan Nusantara Global, 2026)
The Smallholder Oil Palm Replanting Program is one of the national strategic policies aimed at improving the productivity and welfare of oil palm farmers by replacing damaged or aged oil palm trees with certified high-yielding seeds and implementing good agricultural practices. This program has been implemented since 2019 in Gunung Megang Subdistrict, Muara Enim Regency; however, no research has yet been conducted to quantitatively measure the impact of this program on increasing farmers’ productivity and income after the plants enter the productive phase. The study employed a survey method using a descriptive and comparative quantitative approach involving 85 respondents selected via simple random sampling. Data analysis was performed using descriptive statistics, a paired-sample t-test, and effect size. The research results show that the Smallholder Oil Palm Replanting Program has been proven to increase oil palm plantation productivity by 13.73 metric tons of fresh fruit bunches (FFB) per hectare per year by 2025. However, oil palm plantation productivity has not yet reached its potential of 15–17 metric tons per hectare per year for 5–6-year-old trees. The results of the paired-sample t-test indicate that the Smallholder Oil Palm Replanting Program has a significant effect on increasing farmers’ productivity and income.